تعليم مهارة الاستماع بأسلوب الخريطة الذهنية بالتطبيق على طلاب جامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج - Naseha, Siti Durotun; Hasan, Laili Mas Ulliyah; Rahmawati, Chusnia (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
This study discusses learning listening skills using the Mind Maping method for 3rd semester Arabic Language Education students at UIN Malang at UIN Maulana Malik Ibrahim Malang. This study aims to determine the application and effectiveness of the application of concept maps in learning listening skills for students of Arabic Language Education Study Program UIN Malang semester 3. This research uses quantitative methods with data collection techniques namely questionnaires, interviews, observation and documentation. The analytical technique used is a Likert scale. The results showed that learning listening skills using the concept map method was good in both classes, namely 58.3% and 41.6% of the 4 Likert scale standards used.